1997
DOI: 10.1165/ajrcmb.16.4.9115747
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protein tyrosine kinase inhibitors on contractility of isolated bronchioles of the rat.

Abstract: The role of protein tyrosine kinases (PTK) in modulating contractility has not been investigated in airway smooth muscle (ASM). We have examined the effects of the PTK inhibitors ST638, genistein, and tyrphostin A47 on contractions induced by carbachol, serotonin, ionomycin, and 75 mM KCl in isolated bronchioles of the rat with internal diameters of 614 +/- 16 microm (small, n = 143), and 1,433 +/- 39 microm (large, n = 57). ST638 caused a dose-dependent decrease in the maximum response to carbachol, and shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…However, studies with platelets (30,31,34), fibroblasts (20), and colonic smooth muscle (10,13) have suggested that depletion of intracellular calcium stores induces calcium influx across the plasma membrane via a PTK-dependent mechanism. Moreover, inhibitors of PTKs have been shown to inhibit contractions of isolated bronchioles of the rat (9). In the present study, genistein and ST-638 did partially inhibit recovery of S2/S1 during 80 s of refilling.…”
Section: Discussionsupporting
confidence: 57%
“…However, studies with platelets (30,31,34), fibroblasts (20), and colonic smooth muscle (10,13) have suggested that depletion of intracellular calcium stores induces calcium influx across the plasma membrane via a PTK-dependent mechanism. Moreover, inhibitors of PTKs have been shown to inhibit contractions of isolated bronchioles of the rat (9). In the present study, genistein and ST-638 did partially inhibit recovery of S2/S1 during 80 s of refilling.…”
Section: Discussionsupporting
confidence: 57%
“…It is now generally accepted that bronchoconstriction of such small bronchioles plays an important role in the increase in airway resistance that is elicited by agonists (Moreno et al 1986), and by inference also in asthma. However, although some animal studies have suggested that there may be significant differences in the pharmacological and mechanical function of airways from different parts of the bronchial tree (Fleisch & Calkins, 1976;Fujiwara et al 1988;Gauthier et al 1992;Mustafa et al 1994;Chopra et al 1994Chopra et al , 1997, there have been very few in vitro studies of any type on human small bronchioles. Moreover data obtained from non-human species may not necessarily reflect the situation in human ASM, as we have previously described significant differences between the electrophysiology of ASM from human airways and that of other species (Snetkov et al 1995(Snetkov et al , 1996(Snetkov et al , 1998.…”
Section: Resultsmentioning
confidence: 99%
“…Enhanced Ca 2ϩ mobilization and contraction of ASM may contribute to airway hyperresponsiveness (21). Several studies have shown that inhibition of tyrosine kinases impairs the ability of gastric, vascular, and ASM rings or strips to contract on stimulation with agonists acting on GPCRs (3,4,28). Using cultured ASM cells to avoid the possible compounding effects of other cells present in these preparations, we have shown that tyrosine kinases may have a direct effect on ASM contraction and Ca 2ϩ signaling evoked by 5-HT (24).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in smooth muscle, in which Ca 2ϩ is the main determinant of contraction and in which the majority of contractile agonists act through GPCRs, tyrosine kinases may modulate contractility and potentially contribute to the altered smooth muscle responsiveness observed in such diseases as asthma or hypertension. Indeed, it has been reported that contraction of vascular and airway smooth muscle (ASM) depends, at least partially, on tyrosine kinase activity (3,4,28). However, it is not clear how much of this effect is the result of the modulation of Ca 2ϩ signaling or which tyrosine kinases are involved.…”
mentioning
confidence: 99%